Analisis Kemampuan Berpikir Kritis Matematis : Dampak Pendekatan Saintifik ditinjau dari Kemandirian Belajar - Yanwar, Alkat; Fadila, Abi (Desimal: Jurnal Matematika, 2019)
The purpose of this study is to find out whether there are: (1) the influence of the scientific approach on students’ critical thinking skills; (2) the influence of learning independence on students’ mathematical critical thinking ability; (3) the interaction between the scientific approach and the learning independence of students’ critical thinking skills. This research is a quasy experimental design research with 2x3 factorial design. Sampling technique in this research use probability sampling with cluster random sampling. The research instrument used is questionnaire self-reliance learning and test of critical thinking ability mathematically. Data from the results of tests of mathematical critical thinking ability were analyzed using anava test of two unequal cell paths and further tests using a double comparison test with the Scheffe method. The results showed that: (1) there was an influence of the scientific approach on students’ critical thinking skills; (2) there is influence of learning independence to students’ critical thinking ability mathematically; (3) there is no interaction between the scientific approach and the learning independence of mathematical critical thinking skills.